2011
DOI: 10.1093/jxb/err282
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like properties of tobacco plastid thioredoxins f and m

Abstract: Thioredoxins (Trxs) are ubiquitous disulphide reductases that play important roles in the redox regulation of many cellular processes. However, some redox-independent functions, such as chaperone activity, have also been attributed to Trxs in recent years. The focus of our study is on the putative chaperone function of the well-described plastid Trxs f and m. To that end, the cDNA of both Trxs, designated as NtTrxf and NtTrxm, was isolated from Nicotiana tabacum plants. It was found that bacterially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 77 publications
3
47
0
Order By: Relevance
“…Hence, the question of the nature of the physiological targets and roles of all these proteins should now be addressed using other approaches, such as the study of knockout and knockdown plants and in vivo or in vitro methods to identify protein partners. For instance, besides their usual disulfide reductase activity, it has recently been shown that some plastidial Trxs f and m have chaperone properties (Sanz-Barrio et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the question of the nature of the physiological targets and roles of all these proteins should now be addressed using other approaches, such as the study of knockout and knockdown plants and in vivo or in vitro methods to identify protein partners. For instance, besides their usual disulfide reductase activity, it has recently been shown that some plastidial Trxs f and m have chaperone properties (Sanz-Barrio et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Identification of catalase3 (AtCAT3) as one of the interacting proteins with GmTRX seems to support this scenario. Recent reports of the redox-independent, chaperone function of thioredoxins in E. coli, tobacco (N. tabacum), and Arabidopsis (Kern et al, 2003 ;Kthiri et al, 2008;Lee et al, 2009;Park et al, 2009;Sanz-Barrio et al, 2012) have provided a new insight into their diverse physiological roles. A novelty in our present finding is the potential role of GmTRX as a cytoplasmic chaperone largely specific for proteins targeted to peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal aggregation of MDH was performed as described Park et al, 2009;Sanz-Barrio et al, 2012). MDH was incubated in 50 mM HEPES-KOH (pH 8.0) buffer at 43C with various concentrations of GmTRX (molar ratios of GmTRX to MDH of 1:1, 2:1 and 4:1).…”
Section: Chaperone Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, TRXm protein (Guelette et al, 2012; this study) and mRNA (Deeken et al, 2008) accumulate in phloem exudates, and TRXm1 and TRXm4 contribute to SAR (this work). How these proteins contribute to SAR remains to be determined, but recent evidence demonstrating the molecular holdase/foldase activity of NtTRXm in tobacco suggests that TRXm proteins act as molecular chaperones that protect target proteins during stress (Sanz-Barrio et al, 2012). As such, TRXm proteins may protect redox-sensitive proteins important for SAR in the phloem.…”
Section: Proteins Enriched In Sar-induced Phloem That Contribute To Tmentioning
confidence: 99%